Digitalization of Marketing of Soppeng Regency's Competitive Commodities through the Development of the Makassar Vegetables Delivery (VMD) System: Digitalisasi Pemasaran Komoditas Unggulan Kabupaten Soppeng Melalui Pengembangan Sistem Vegetables Makassar Delivery (VMD) - Djam'an, Nurwati; Wulandari, Sri Riski; Fitriwati; Muhammad Junaid; Ade Kusmaladi (Yayasan Ahmar Cendekia Indonesia, 2024)
This digitization training of commodity trading as efforts to digitalize the marketing of competitive commodities in Soppeng Regency, South Sulawesi, with a focus on the Tampaning chili. Soppeng Regency, which relies on the agricultural sector as the main economic driver, faces challenges in marketing agricultural products, especially chili. To overcome this, The Student Community Service- Community Empowerment by Students Programme (KKN PMM) of Universitas Negeri Makassar carry out system development, socialization, training in use, and marketing through the Vegetables Makassar Delivery (VMD) system. This activity was carried out in Bulue Village, in collaboration with local farmer groups and the Food Crops, Horticulture, Plantation and Food Security Office. The methods used include system development, socialization, and training on the use of VMD applications, and product packaging and sales. The results show that the VMD system has the potential to improve added value of the commodities, to increase society income and to improve Soppeng Regency's economic conditions. Abstrak Pelatihan inimerupakan upaya digitalisasi pemasaran komoditas unggulan di Kabupaten Soppeng, Sulawesi Selatan, dengan fokus pada tanaman cabai Tampaning. Kabupaten Soppeng, yang mengandalkan sektor pertanian sebagai penggerak ekonomi utama, menghadapi tantangan dalam pemasaran produk pertanian, khususnya cabai. Untuk mengatasi hal ini, mahasiswa KKN PMM Universitas Negeri Makassar melakukan pengembangan sistem, sosialisasi, pelatihan penggunaan, dan pemasaran melalui sistem Vegetables Makassar Delivery (VMD). Kegiatan ini dilaksanakan di Desa Bulue, berkolaborasi dengan kelompok tani lokal dan Dinas Tanaman Pangan, Hortikultura, Perkebunan dan Ketahanan Pangan. Metode yang digunakan meliputi pengembangan system, sosialisasi, pelatihan penggunaan aplikasi VMD, dan pengemasan dan penjualan produk. Hasil menunjukkan bahwa sistem VMD berpotensi meningkatkan nilai jual komoditas, meningkatkan pendapatan dan meningkatkan pertumbuhan ekonomi masyarakat di Kabupaten Soppeng.